Crossed Non-Dominant Hemisphere Syndrome in a Right-Hander - M. Fujimori; K. Wakisaka; A. Yamadori; T. Imamura; T. Uehara; K. Yamashita; M. Tabuchi (Behavioural Neurology)
A right-handed patient with a large left temporo-parietal infarction manifested various non-dominant hemisphere signs. He had two left-handed children. On neurobehavioural examinations, he did not show aphasia or ideomotor apraxia, but did show hemispatial neglect, spatial agraphia, constructional apraxia, auditory and tactile extinction, anosodiaphoria and affective changes, all of which are usually observed after right hemispheric damage. We conclude that he has a reversed cerebral laterality of cognitive functions and showed crossed non-dominant hemisphere syndrome.